Simulating super earth atmospheres in the laboratory. Issue 1 (20th May 2015) - Claudi, R.; Erculiani, M. S.; Galletta, G.; Billi, D.; Pace, E.; Schierano, D.; Giro, E.; D'Alessandro, M.
Abstract: Several space missions, such as JWST, TESS and the very recently proposed ARIEL, or ground-based experiments, as SPHERE and GPI, have been proposed to measure the atmospheric transmission, reflection and emission spectra of extrasolar planets. The planet atmosphere characteristics and possible biosignatures will be inferred by studying planetary spectra in order to identify the emission/absorption lines/bands from atmospheric molecules such as water (H2 O), carbon monoxide (CO), methane (CH4 ), ammonia (NH3 ), etc. In particular, it is important to know in detail the optical characteristics of gases in the typical physical conditions of the planetary atmospheres and how these characteristics could be affected by radiation driven photochemical and biochemical reaction. The main aim of the project 'Atmosphere in a Test Tube' is to provide insights on exoplanet atmosphere modification due to biological intervention. This can be achieved simulating planetary atmosphere at different pressure and temperature conditions under the effects of radiation sources, used as proxies of different bands of the stellar emission. We are tackling the characterization of extrasolar planet atmospheres by mean of innovative laboratory experiments described in this paper. The experiments are intended to reproduce the conditions on warm earths and super earths hosted by low-mass M dwarfs primaries with the aim to understand if a cyanobacteria population hosted on a Earth-like planet orbiting an M0 star is able to maintain its photosynthetic activity and produce traceable signatures.